Assessing the application of ratios between daily and sub-daily extreme rainfall as disaggregation coefficients. (December 2022) - Abreu, Marcel Carvalho; Pereira, Silvio Bueno; Cecílio, Roberto Avelino; Pruski, Fernando Falco; Almeida, Laura Thebit de; Silva, Demetrius David da
Abstract: The objective of this paper was to establish disaggregation coefficients for the state of Minas Gerais, Brazil, under the premises of i) stationarity of the disaggregation coefficients according to the return period and ii) spatial validation of the disaggregation coefficients. The regression analysis was used as a statistical procedure to verify the significance of the coefficients of disaggregation slope coefficient as a function of return period in daily and sub-daily rainfall time series in rain gauges distributed throughout the state of Minas Gerais. Most of the disaggregation coefficients (94% of the situations) did not show a tendency to change due to the return period. The detected trends modified coefficients of disaggregation by up to 21% to the average obtained for different return periods. It was also verified that there is a significant difference between rainfall ratios of different durations, for different locations, indicating that the coefficients of disaggregation are not regional, but rather local. The use of disaggregation coefficients to obtain sub-daily rainfall is possible, provided that the representative coefficients of the locality are used. In this context, the spatialization of disaggregation coefficients is an important approach. Highlights: Relations between rainfall of different durations are disaggregation coefficients. The use of disaggregation coefficients to obtain sub-daily rainfall is possible. Disaggregation coefficients did not show a trend to change due to return period. The disaggregation coefficients have local validity. The spatialization technique can favor suitable disaggregation coefficients.